2017
DOI: 10.1007/s10928-017-9558-5
|View full text |Cite|
|
Sign up to set email alerts
|

Scientific white paper on concentration-QTc modeling

Abstract: The International Council for Harmonisation revised the E14 guideline through the questions and answers process to allow concentration-QTc (C-QTc) modeling to be used as the primary analysis for assessing the QTc interval prolongation risk of new drugs. A well-designed and conducted QTc assessment based on C-QTc modeling in early phase 1 studies can be an alternative approach to a thorough QT study for some drugs to reliably exclude clinically relevant QTc effects. This white paper provides recommendations on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
309
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(327 citation statements)
references
References 34 publications
4
309
0
1
Order By: Relevance
“…Our results also need to be considered independent of the concentration–QTc interval analysis [9, 14]. While concentration–QTc interval analysis is a powerful tool in the assessment of drug-induced QTc interval changes, its successful application is based on the validity of the QTc interval values.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also need to be considered independent of the concentration–QTc interval analysis [9, 14]. While concentration–QTc interval analysis is a powerful tool in the assessment of drug-induced QTc interval changes, its successful application is based on the validity of the QTc interval values.…”
Section: Discussionmentioning
confidence: 99%
“…The International Conference on Harmonization (ICH) E14 guideline for the TQT study states that the “threshold level of regulatory concern…is around 5 ms as evidenced by an upper bound of the 95% credible interval (CI) around the mean effect on QTc of 10 ms.” Overall, incorporation of these preclinical and clinical tests has been widely credited with the reduction in drugs with pro‐arrhythmic risk, but the high cost of the TQT study, estimated to be 1–4 million dollars, has led to efforts to develop both clinical and preclinical alternatives. For instance, both the ICH and the US Food and Drug Administration (FDA) now allow an alternative TQT study that involves concentration‐QTc (C‐QTc) modeling of QTc data collected in early phase I studies …”
mentioning
confidence: 99%
“…We have previously shown that iPSC‐derived cardiomyocytes from a moderate‐sized sample of healthy subjects ( n = 27) are a highly reproducible in vitro population model . Notably, this sample size is greater than those recommended to control false negatives in C‐QTc modeling‐based TQT studies . We, therefore, hypothesized that the C‐QTc modeling of iPSC‐derived cardiomyocytes from a diverse sample of human subjects can serve as a “TQT study in a dish.” To test this hypothesis, we first investigate whether a population‐based in vitro model in combination with in silico pharmacodynamic (PD) modeling can predict the clinical C‐QTc relationship ( Figure a ).…”
mentioning
confidence: 99%
“…This was followed by the ICH E14 Guideline: The Clinical Evaluation of QT/QTc Interval Prolongation and Proarrhythmic Potential for Non‐Antiarrhythmic Drugs Questions & Answers (R3) document (December 2015), which was used in the design of the present analysis. Since then, a white paper has proposed an easier approach to concentration‐QT analysis . This newer approach suggests the use of a more efficient method using data from the single‐ascending‐dose and repeat‐ascending‐dose studies only.…”
Section: Discussionmentioning
confidence: 99%